2019
DOI: 10.3138/jvme.0717-097r
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Simulation Training in Anesthesia on Student Operational Performance and Patient Safety

Abstract: A veterinary anesthesia simulated environment (VASE) with clinical scenarios has been integrated into the pre-clinical curriculum at Midwestern University College of Veterinary Medicine to simulate anesthesia of a live patient within a surgical suite. Although this modality was shown to significantly improve veterinary students’ perceived preparedness to perform anesthesia on live patients, whether this would improve anesthesia competency in the actual clinical environment, described as operational performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In addition, preventing or reducing the pressure imposed on students is a valuable tool because this pressure can also influence student memory and learning 3 . According to Jones et al, 12 the students feel calmer and more confident in carrying out skills acquired through simulations, and these skills are brought into clinical care in real life, allowing students to feel greater calm and confidence and allowing a reduction in errors in the resolution of complications. Jesus et al 13 also observed that realistic simulation generates extensive knowledge for students regarding the development of competencies for critical reasoning, carrying out correct actions and correcting errors without compromising the lives of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preventing or reducing the pressure imposed on students is a valuable tool because this pressure can also influence student memory and learning 3 . According to Jones et al, 12 the students feel calmer and more confident in carrying out skills acquired through simulations, and these skills are brought into clinical care in real life, allowing students to feel greater calm and confidence and allowing a reduction in errors in the resolution of complications. Jesus et al 13 also observed that realistic simulation generates extensive knowledge for students regarding the development of competencies for critical reasoning, carrying out correct actions and correcting errors without compromising the lives of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies described in the reviewed articles appear to document that simulators can be used effectively to improve student skills in performing certain practical tasks. [29][30][31]34,[38][39][40]42,50,52,58,67,71,74,76,[80][81][82][83][84]86,88 The time taken to carry out a surgical procedure, as well as the respective performance scores of students using simulators, have been correlated with live surgical performance and procedure times. 15,89 Training on models has been shown to achieve learning outcomes that are equivalent 86 or superior 71,72,78,82 to those achieved through the use of cadaver or live animal practical classes.…”
Section: Simulator Efficacymentioning
confidence: 99%
“…However, the studies that have been carried out suggest that students who have undertaken such training perform better than those who have not. For example, one study demonstrated that anaesthesia simulation training in the preclinical veterinary curriculum significantly improved students' clinical competency and the safety of their patients 19 . In another study, students initially trained using a model were faster and more accurate when placing an intravenous catheter in a live horse than students who trained on a live horse 20 …”
Section: Name Of Resource Url (Accessed 10 May 2021)mentioning
confidence: 99%
“…For example, one study demonstrated that anaesthesia simulation training in the preclinical veterinary curriculum significantly improved students' clinical competency and the safety of their patients. 19 In another study, students initially trained using a model were faster and more accurate when placing an intravenous catheter in a live horse than students who trained on a live horse. 20 In conclusion, although veterinary virtual simulation tools are still in their infancy, they are already transforming veterinary education.…”
Section: What You Need To Knowmentioning
confidence: 99%